STUDI TENTANG SUPERVISI AKADEMIK DALAM UPAYA PENINGKATAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM PADA SEKOLAH MENEGAH PERTAMA DI KABUPATEN TANGERANG - Girmono, Girmono; Putra, Nusa; Fattah, Nanang (Ta’dibuna: Jurnal Pendidikan Islam, 2017)
The purposes of this study are: First, to know how the role of supervisors in supervising learning administrations and academic supervision to Islamic education teachers at school. Second, to know supervisors’ performance based on standard. Third, to know the handicaps in doing supervisors’ duties. Fourth, to know supervisors’ strategy in solving the problems. The Method used in this research is descriptive analysis with qualitative approaches. Based on the research goals above, it can be conluded: First, based on document analysis and teachers’ administration observation that teachers have had complete documents as guide lines in doing teaching learning process. However, most of teachers still adopted lesson planning they made from other schools. Second, that the supervisors of Islamic Relegious Education in doing their tasks is not maximum yet, such as monitoring eight national standards of education and assessing teachers’ performance. There are even other tasks, such as the activity of guiding and evaluating professional teachers which were not carried out. Third, the handicaps faced by supervisors were (1) the teachers who were absent in teachers’ forum, (2) the difficulties of changing teachers’ mindset in arranging program, and (3) the weakness of mastering Information Communication Technology. Fourth, the solutions offered are (1) the supervision goal is supposed to be communicated and comprehended by teachers, principals, and supervisors, (2) the supervision should be well-planned, constructive, and democratic, (3) the teachers should be involved in the process of planning and implementing supervision so that they understand procedures and advantages of supervision in developing their professionalism, (4) the supervision program should motivate to the changes in the teaching learning activity. Kata kunci: supervisi, akademik, PAI, profesionalisme.